A biocompatible PAA-Cu-MOP hydrogel for wound healing. Issue 59 (1st October 2020) - Chen, Linlin; Qin, Yu; Cheng, Jing; Cheng, Yi; Lu, Zhixiang; Liu, Xiaolan; Yang, Shaoxiong; Lu, Shuhan; Zheng, Liyan; Cao, Qiue
Abstract : PAA-Cu-MOP hydrogel prepared by a facile mixing and ultrasonic procedure showed an excellent wound healing behavior which was better than that of commercial recombinant human epidermal growth factor. Abstract : Wounds infected by bacteria are dangerous for human beings. However, along with the emergence of new strains and strong bacterial resistance, traditional antibiotics are unable to meet the medical needs for treating bacterial infections. Thus, new antibacterial substances with superior antimicrobial properties are urgently needed. Herein, a hydrogel containing poly acrylic acid (PAA), glycerol and Cu-MOP (named PAA-Cu-MOP hydrogel) is obtained by a facile mixing and ultrasonic procedure for wound healing treatment. This PAA-Cu-MOP hydrogel with high biocompatibility exhibits excellent wound healing behavior and is even better than the one of recombinant human epidermal growth factor. Tissue experiment results reveal that the PAA-Cu-MOP hydrogel accelerates the wound healing process by promoting angiogenesis, stimulating cell proliferation, and up-regulating cell factors.